Women in STEM in Higher Education Good Practices of Attraction, Access and Retainment in Higher Education - García-Peñalvo, Francisco José; García-Holgado, Alicia; Dominguez, Angeles; Pascual, Jimena (Lecture Notes in Educational Technology, 2022)
This open access book addresses challenges related to women in STEM in higher education, presenting research, experiences, studies, and good practices associated with the engagement, access, and retention of women in the STEM disciplines. It also discusses strategies implemented by universities and policymakers to reduce the existing gender gap in these areas. The chapters provide an overview of implementations in different regions of the world and provide numerous examples that can be transferred to other higher education institutions.